Inactive Fusarium Fungal strains (ZSY and MJY) isolation and application for the removal of Pb(II) ions from aqueous environment - Long, Jianyou; Yuvaraja, Gutha; Zhou, Shuyi; Mo, Jianying; Li, Huosheng; Luo, Dinggui; Chen, Di Yun; Kong, Lingjun; Subbaiah, Munagapati Venkata; Reddy, Guda Mallikarjuna (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •Two inactive fungal strains (ZSY and MJY) were isolated and utilized as an effective biosorbent for the removal of Pb(II) ions from aqueous environment.•The FTIR results revealed that hydroxyl (OH), amine (NH2) and carbonyl (CO) functional groups present on the surfaces of ZSY and MJY.•The kinetic and equilibrium data fitted well with pseudo-second-order kinetic model and Langmuir isotherm model.•Thermodynamic study showed that the Pb(II) adsorption is endothermic, feasible and spontaneous nature of the adsorption process. In this study, two Fusarium strains namely ZSY and MJY were successfully isolated from the contaminated soil of Dabaoshan smelter in Shaoguan City, and utilised as a biosorbent for the removal of Pb(II) ions from aqueous solution. Effect of pH (6), agitation speed (150rpm), biomass concentration (1g/L), initial Pb(II) concentration, contact time (60min), and effect of temperature (323K) was investigated. Kinetic and isotherm results showed that the removal of Pb(II) ions onto ZSY and MJY were fitted well with the pseudo-second-order and Langmuir isotherm models (232.56 and 263.16mg/g). In addition thermodynamic studies were also discussed.